Adaptation and validation of the Washington group/unicef child functioning module in a nationally representative sample of Canadian children and youth - Emma Nolan; Katherine Cost; Ryan Miller; Li Wang; Chen Yun-Ju; Jordan Edwards; Eric Duku; Stelios Georgiades; Peter Szatmari; Harriet MacMillian; Charlotte Waddell; Katholiki Georgiades (BMC Public Health)
Abstract Background The Washington Group/UNICEF Child Functioning Module (WG/UNICEF CFM) was developed to identify children and youth with disabilities by assessing functional difficulties. This study focuses on the cognitive, emotional, and behavioral components of the WG/UNICEF CFM, as these domains are particularly relevant to understanding child and youth mental health and developmental functioning. The objective of this study was to examine the latent structure of these domains using a graded response scale in a nationally representative sample of Canadian children and youth aged 5–17 years and to evaluate how this approach captures the dimensional nature of functional difficulties. Methods Data for analyses come from the 2019 Canadian Health Survey on Children and Youth (n = 33,420). Survey data were collected by Statistics Canada using an electronic questionnaire that was either self-completed online or interviewer-administered by telephone. To assess the latent structure of the WG/UNICEF CFM, analyses were conducted in four linked phases focusing on the following 9 domains: self-care, communication, learning, remembering, concentrating, accepting change, behavior, relationships, and emotions. An exploratory factor analysis (EFA) was conducted first, followed by, confirmatory factor analysis (CFA), then evaluations of measurement invariance across age and sex and external validity using structural equation modeling and instrumental variables. Results Results indicated that a two-factor model best described the data, χ2(26, N = 16,810) = 619.076, p < 0.002, CFI = 0.98, TLI = 0.97, RMSEA = 0.037). Factor one represented Cognitive, Behavioural and Interpersonal Functional Difficulties; while Factor two represented Emotional Functional Difficulties. The construct validity tests supported the distinction between the two factors by demonstrating stronger associations with instrumental variables measuring similar underlying constructs. Conclusions This study extends existing research by demonstrating the utility of the WG/UNICEF CFM in assessing cognitive, behavioral, interpersonal, and emotional functional difficulties at the population level in a high-income country. The measure’s strong psychometric properties, ease of use, and cost-free administration support its applicability in general population health surveys of children and youth. Findings highlight the value of a dimensional approach to functional difficulties, offering a more comprehensive understanding of population-level variations in functioning. Integrating this measure into large-scale surveys can facilitate trend monitoring, improve data-driven policy interventions, and support strategic planning for education, healthcare, and social services. These insights contribute to optimizing resource allocation and ensuring equitable access to services that address the diverse functional needs of children and youth.